Prospective Analysis on Survival Outcomes of Nonsmall Cell Lung Cancer Stages over Ⅲb Treated with HangAm-Dan - JEONG, Tae-Young (Zhongguo Fei Ai Za Zhi, 2010)
BACKGROUND AND OBJECTIVE: Non-small cell lung cancer (NSCLC) stages over Ⅲb still remain as an intractable disease. Survival rate of NSCLC stages over Ⅲb could be increased through chemotherapy and radiation, but results are not satisfactory. Oriental medicine herbal formula, HangAm-Dan (HAD) has been developed for anti-tumor purpose and several previous studies have already reported its effects. The aim of this study is to assess HAD's efficacy on prolonging the survival rate of NSCLC stages over Ⅲb. METHODS: We have administered 3 000 mg of HAD daily to patients. The study included 74 first visit patients of East-West Cancer Center (EWCC) from November 2007 to April 2008, diagnosed with inoperable NSCLC stages over Ⅲb. Among them, 30 patients were in HAD group and 44 patients were in combined group with conventional therapy and HAD. We have observed and analyzed their overall survival. RESULTS: Of total 74 patients, overall 1 year, 2 year survival rates and the median survival time were 62.1%, 34.9% and 17.0 months (95%CI: 12.9-21.1). NSCLC stage Ⅲb patients showed higher survival rates than NSCLC stage Ⅳ patients (P=0.408). The 1 year, 2 year survival rates and the median survival time of the combined group were 70.5%, 37.9% and 20.0 months (95%CI: 16.4-24.6). In HAD group, the 1 year, 2 year survival rates and the median survival time were 50.0%, 25.7% and 12.0 months (95%CI: 6.6-17.4). The combined therapy group showed higher survival rates than the HAD group (P=0.034). Each groups treated with HAD for more than 4 weeks showed higher survival rates than those treated for less than 4 weeks, but there was no significant difference (P=0.278). In hazard ratio, the combined therapy group showed lower mortality rate than the HAD group with statistical significance (P=0.040). CONCLUSION: HAD could prolong the survival rate of inoperable NSCLC stages over Ⅲb. HAD is more effective when combined with conventional therapy. In the future, more controlled clinical trials with larger sample in multi-centers are needed to reevaluate the efficacy and safety of HAD.